PERAN DINAS KOMUNIKASI DAN INFORMATIKA DALAM KETERBUKAAN INFORMASI PUBLIK DI KABUPATEN SIDOARJO - Charista Diva Vernanda; Ilmi Usrotin Choiriyah (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to analyze and describe the role of the Sidoarjo Regency Communication and Informatics Office in public information disclosure using a descriptive qualitative approach and data collection is done by observation, interviews, and documentation. Research informants were determined by purposive sampling technique with informants as the head of the field of information management and public communication and public relations officers. The research aims to find out how the role of the Communication and Information Technology Office can carry out information disclosure for public needs in Sidoarjo Regency, because information disclosure is a crucial principle and one of the characteristics of good governance principles. Sidoarjo and Diskominfo were chosen because they showed seriousness in encouraging public information disclosure to the public, this can be seen from the results found that Diskominfo carried out desk review activities on the list of public information and facilitated the village.id domain to encourage information disclosure, but in several other indicators found internal challenges such as employee loyalty that can affect the totality of performance and still lack of community participation response is one of the challenges in information disclosure.